O princípio da autonomia da vontade como garantia da moralidade em Kant - Borges, José Francisco Martins (2007)
The current dissertation is the result of an investigation about the principle of the autonomy of the will. According to Immanuel Kant, the autonomy is the foundation of all morality of the human actions. The autonomy consists in the presentation of the reason for herself of a moral law valid for the will of all rational beings. The moral law is going against the actions that are practiced by selfishness, since she possesses the form of an universal legislation that is expressed in the categorical imperative of the reason. The heteronomy of the will is the principle contrary to the autonomy. Starting from the determination of your will for the moral law the man becomes conscious of your freedom. Consequently, the freedom is what turns possible to the man your self-determination for the moral action.